The Development of an Online Surveillance of Digital Media Use in Early Childhood Questionnaire- SMALLQ™- For Singapore - Michael Yong Hwa Chia; Lee Yong Tay; Terence Buan Kiong Chua (Montenegrin Sports Academy, 2019)
Digital media engagement in families in Singaporean society is increasing at an unprecedented pace. Limited research in the last five years in Singapore shows that young children experience significant amounts of screen time from television, computers and other forms of mobile digital devices, even before primary school. For children, digital media use can aid with learning, but its overuse has inimical effects on learning and health. As digital media use in children increases faster than research on its impact, it is essential to develop a tool that can monitor changes in digital media habits of children over time. This study aimed to develop an online questionnaire for parents to report on the digital media habits of children. An online questionnaire bundle, Surveillance of digital-Media hAbits in earLy chiLdhood Questionnaire (SMALLQ™), organized into sections ((I) Digital-media use of parent and child, (II) Non-digital media behaviour of the child, (III) Parent and child information) was developed for the purpose of charting digital media use and changes over three years (2018, 2019, and 2020). The results showed that SMALLQ™ has face and content validity and was practicable for Singapore. Furthermore, based upon a similar methodology for developing the SMALLQ™, the development of Child-SMALQ (Surveillance of digital MediA use in chiLdhood questionnaire) and Adolescent-SMALQ (Surveillance of digital MediA use in adoLescence questionnaire) are directions for future research.